Duplicate Vas Deferens Encountered during Inguinal Hernia Repair: A Case Report and Literature Review - Maxwell C. Breitinger; Evan H. Roszkowski; Adam J. Bauermeister; Andrew A. Rosenthal (Case Reports in Surgery)
Duplication of the vas deferens is a rare anomaly, defined as the presence of two distinct vasa deferentia within one spermatic cord, with only 28 cases reported worldwide since 1959. We report the case of a 63-year-old man with a duplicate vas deferens, presenting with abdominal pain from bowel obstruction secondary to incarcerated inguinal hernia. Spermatic cord dissection during hernioplasty revealed duplication of the vas deferens within the right spermatic cord. Doppler ultrasonography confirmed absence of waveforms in both vasa deferentia with arterial signal in the accompanying vessel. The hernia was repaired without complication. This report emphasizes recognition of duplicate vas deferens in avoiding iatrogenic injury and optimizing surgical outcome.